2013
DOI: 10.1155/2013/385892
|View full text |Cite
|
Sign up to set email alerts
|

FlexFT: A Generic Framework for Developing Fault-Tolerant Applications in the Sensor Web

Abstract: Fault-tolerant systems are expected to operate in a variety of devices ranging from standard PCs to embedded devices. In addition, the emergence of new software technologies has required these applications to meet the needs of heterogeneous software platforms. However, the existing approaches to build fault-tolerant systems are often targeted at a particular platform and software technology. The objective of this paper is to discuss the use of FlexFT-a generic component-based framework for the construction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Such limitations can be addressed by adopting a generic approach based on existing standard interfaces such as SWE standards and/or Devices Profile for Web Services(DPWS) [17], [18]. Although several applications rely on standard protocols, the communication between sensors and the integration of sensors in highly dynamic scenario in near real-time still is not fully addressed.…”
Section: B Dynamically Integrating Sensors Into the Sensor Webmentioning
confidence: 99%
“…Such limitations can be addressed by adopting a generic approach based on existing standard interfaces such as SWE standards and/or Devices Profile for Web Services(DPWS) [17], [18]. Although several applications rely on standard protocols, the communication between sensors and the integration of sensors in highly dynamic scenario in near real-time still is not fully addressed.…”
Section: B Dynamically Integrating Sensors Into the Sensor Webmentioning
confidence: 99%
“…The main differential of this study was to explore how the componentization of software, mixed with software diversity techniques (N-Versions programming), can be used in WSN both to create self-adaptive lowpower applications and to develop fault-tolerant applications. To achieve different levels of self-organization and fault tolerance, it was necessary to integrate various approaches and solutions previously proposed, among them, the protocol DAARP 16 and the frameworks: FlexFT, 23 OpenCOM, 24 and Sinalgo. 22 The objective of this work was not to develop the best fire detection solution, considering that a strong group of heterogeneous professionals is required in the development process.…”
Section: Concluding Remarks and Future Workmentioning
confidence: 99%
“…This framework allows for the reuse and integration of produced data with other data resources, which enables spatial business intelligence for various domain-specific applications. Similarly, [23] discussed the use of FlexFT, which is a generic component-based framework for the construction of adaptive fault tolerant systems that can integrate and reuse technologies and deploy them across heterogeneous devices.…”
Section: Models and Architectures For Sensorsmentioning
confidence: 99%
“…FlexFT provided a standardized and interoperable interface for sensor observations by relying upon the "Sensor Web" paradigm established by the Open Geospatial Consortium (OGC). Beder et al [23] implemented a Java prototype to the framework and the authors evaluated the potential benefits through case studies and performance measurements. By implementing and deploying these case studies in standard PCs as well as in sensor nodes, authors showed that FlexFT could cope high heterogeneity with minimal resource overheads.…”
Section: Models and Architectures For Sensorsmentioning
confidence: 99%
See 1 more Smart Citation